Participation in culture in the perspective of the European Capital of Culture Wrocław 2016. Report from CATI research with participation of the residents of Wrocław and the region of Lower Silesia - Pluta, Jacek; Banaszak, Ewa; Błaszczyk, Mateusz; Kajdanek, Katarzyna (Instytut Socjologii Uniwersytetu Wrocławskiego)
The report presents results of a year-long research project on the attitudes of the residents of Wrocław and the region of Lower Silesia towards the European Capital of Culture 2016. In three waves of measurement carried out using CATI method the interviewees were asked about their participation in the ECoC events, about individual benefits as well as about their assessment of the organization of the event and the impact it may have on the city. A unique feature of the research was an opportunity to track changes mediated by the ECoC events taking place in the city – they were captured in the following measurements.
Keywords: Europejska Stolica Kultury; Wrocław; społeczne efekty ESK